2004
DOI: 10.1124/dmd.32.3.340
|View full text |Cite
|
Sign up to set email alerts
|

Human PXR Variants and Their Differential Effects on the Regulation of Human Udp-Glucuronosyltransferase Gene Expression

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:The pregnane X receptor (PXR) has three known major transcript variants resulting from alternative splicing. The less well characterized variants T2 and T3 are identical to the well described variant T1 except for a 39-amino acid N-terminal extension in T2 and an internal 37-amino acid deletion in T3. We have developed reverse transcription-polymerase chain reaction (RT-PCR) methods to detect and quantify each human PXR (hPXR) in human l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(92 citation statements)
references
References 27 publications
4
87
1
Order By: Relevance
“…6B). Recently, Gardner-Stephen et al [19] using RT-PCR based approaches have shown three variants of PXR that are expressed in liver and intestinal mucosa. Hence, using PXR antiserum we also investigated the expression of PXR variants in a liver cell line (HepG2) and intestinal adenocarcinoma cell line (COLO) by Western blot analysis.…”
Section: Detection Of Pxr In Transfected Mammalian Cells In Culturementioning
confidence: 99%
“…6B). Recently, Gardner-Stephen et al [19] using RT-PCR based approaches have shown three variants of PXR that are expressed in liver and intestinal mucosa. Hence, using PXR antiserum we also investigated the expression of PXR variants in a liver cell line (HepG2) and intestinal adenocarcinoma cell line (COLO) by Western blot analysis.…”
Section: Detection Of Pxr In Transfected Mammalian Cells In Culturementioning
confidence: 99%
“…However, due to the use of heterologous promoters, these models do not provide bona fide levels of expression of PXR or CAR in all tissues of the mouse. Furthermore, splice variants of hPXR and hCAR have recently been described, some of which have been shown to have functional activity (19)(20)(21)(22)(23). None of these splice variants are expressed by mouse models in which pure cDNAs are used.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18] However, studies of UGTs in human hepatocytes are limited to only a few investigations. Assessments of UGT induction by several human UGT substrates has demonstrated that the primary human hepatocyte model is highly suitable for the investigation of UGT regulation.…”
Section: Introductionmentioning
confidence: 99%